Pharmacology Curriculum and Career Option in dental and Basic Medical Sciences: Graduating Dental Students’ Perspective under Kathmandu University in Nepal - Paudel, KR; Sharma, M (Asian Journal of Medical Sciences, 2013)
Objective: Present study was aimed to obtain the graduating dental students’ view on current pharmacology curriculum for Bachelor of Dental Surgery (BDS) under Kathmandu University (KU) and their perspective on preclinical and dental sciences as future career opportunity. Materials and Methods: This was questionnaires based observational study among BDS students. Forty eight completed questionnaires were collected and analyzed. Chi square test was used whenever applicable and level of significance was set at 5%. Results: Student views showed that present pharmacology curriculum under KU is enough (62.5%, P<0.001) though the relevance of the course is variable. Significantly higher number of students opined that pharmacology should be taught beyond first and second years (54.2%, P<0.001). More students wanted to pursue post graduation in dental sciences (75%, P<0.001). Subject of choice in preclinical science was forensic medicine (37.5%, P<0.001) followed by pharmacology (25%, P<0.001) whereas it was orthodontics and prosthodontics (20.8%, P<0.05) followed by conservative dentistry and endodontics (16.7%, P<0.05) in dental sciences. Conclusion: On graduating dental students’ view, current pharmacology curriculum is enough and inclusion of pharmacology subject beyond first and second years can be considered. Their career option was 75% in dental sciences and 12.5% in basic medical sciences for post graduation. DOI: http://dx.doi.org/10.3126/ajms.v5i2.8645 Asian Journal of Medical Science, Volume-5(2) 2014: 106-112